اثر المعاهدات الدولية و ألاقليمية على القوانين الداخلية: حقوق الاقليات نموذجاً (دراسة تحليلية مقارنة) - Saed, Dr. Raqeeb Ham Rashid; Abdullah, Dr. Khamosh Omar (Journal of Legal and Political Studies, 2025)
Regional and international treaties are instrumental in shaping domestic legal frameworks, especially when deployed to protect minority rights. This article examines the influence of treaties like the ICCPR and MICE on domestic legal systems and implementation challenges using case studies to demonstrate their impact. According to the findings, despite international treaties’ significance in providing a solid legal foundation for protecting minority rights, political resistance, legal ambiguities and weak enforcement challenges continue to undermine their implementation in domestic legal systems. Case studies from Central Europe and Canada highlight both the challenges and successes of incorporating international treaties into domestic laws. Consequently, this study underscores the importance of establishing stronger enforcement mechanisms, providing better judicial training and enhancing cross-border cooperation so as to warrant the effective implementation of international treaties across various jurisdictions.
Keywords: Keywords Domestic legal reforms; Human rights enforcement; International law; Legal integration; Minority rights; Regional treaties